2010
DOI: 10.1016/j.exer.2009.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of aquaporins 1 and 4 coincides with neurodegenerative events in retinas of spontaneously diabetic Torii rats

Abstract: Evidence is mounting that not only microangiopathy, but also neurodegenerative events occur in the retinas of humans and rodents with early diabetes. Diverse pathologies are known to alter the amount and/or location of glial expression of the water-selective channels aquaporins (AQPs) 1 and 4. However, the temporal relationships among glial activation, the altered expression of the AQP proteins and neuronal death in the retinas of diabetic animals remains to be investigated. Male spontaneously diabetic Torii (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 52 publications
(123 reference statements)
3
38
0
1
Order By: Relevance
“…Recent advances in proteome analysis methods have allowed the further exploration and acquisition of vitreous protein profiles [1,6-8]. In the last few years, proteomics has been applied to explore proteins which were differentially expressed in patients with proliferative diabetic retinopathy and in nondiabetic patients [9-14]. Previous studies have identified some proteins that are differentially expressed in the vitreous of PDR patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in proteome analysis methods have allowed the further exploration and acquisition of vitreous protein profiles [1,6-8]. In the last few years, proteomics has been applied to explore proteins which were differentially expressed in patients with proliferative diabetic retinopathy and in nondiabetic patients [9-14]. Previous studies have identified some proteins that are differentially expressed in the vitreous of PDR patients.…”
Section: Introductionmentioning
confidence: 99%
“…farelerde oluşturdukları prematüre retinopati modelinde, AQ1 proteininin dış retinada, özellikle rod ve koni tabakalarında lokalize olduğunu bulmuşlardır. Fukuda ve ark [9] AQP1 ve AQP4'ün diabetik Torii sıçanların iç ve dış retinalarında farklı şekillerde lokalizasyonlarını göstermişlerdir. Bizim çalışmamız da bu bulguları destekler şekilde AQP1'nin diabetik sıçanlardaki artmış ifadesini göstermiştir, Fakat çalış-mamızda AQP1'in immunoreaktivitesinde fark görülmesine rağ-men, diabetik ve diabetik olmayan sıçan retina ve siliyer cisim morfolojilerinde anlamlı bir fark bulunamamıştır.…”
Section: Discussionunclassified
“…Boxes represent the point in the pathway targeted by animal models. Italicized text corresponds to the induced models and bold text corresponds to the genetic models [ 20,[145][146][147][148] SDT QTL Gisdt1, 2, 3 [149][150][151][152][153][154][155] develop proliferative retinopathy [50]. Monkeys thus appear to be surprisingly resilient to induction of DR despite removal of the pancreas, long-term diabetes, and poor control of blood sugar levels.…”
Section: Pancreatectomymentioning
confidence: 99%
“…SDT rats are characterized by retinal dysfunction, which includes retinal detachment with fibrous proliferation, absence of retinal ischemia in the presence of neovascularization, leukostasis, increased number of apoptotic cells in the GCL and INL, vascular lesions, and pericyte loss [151][152][153][154]. A distinct feature of this model is the appearance of large retinal folds with extensive leakage around the optic disc, similar to retinal detachment observed in humans [151][152][153][154]. The SDT rat is the rat model that most closely resembles the pathophysiology seen in humans; however, the absence of microaneurysm makes them a more suitable model for studying NPDR.…”
Section: Rat Genetic Models Of Drmentioning
confidence: 99%